STRATEGI PENINGKATAN KEMAMPUAN TILAWATIL AL- QUR’AN MELALUI PROGRAM DINIYAH (SUATU PENELITIAN PADA SEKOLAH DASAR NEGERI 4 BANDA ACEH) - Helmiati Helmiati (Jurnal Ilmiah Pendidikan Anak (JIPA), 2021)
This research is based on the Diniyah Program. A program that aims to improve the study of Islamic religious knowledge and study the Qur'an. When students have graduated from elementary school (SD), they will get a certificate marking the graduation of the diniyah program and if the student has obtained this certificate, then when they continue their school to the SMP / MTSN level, they will no longer be taking the al-Qur'an reading test. However, this rule only applies to the city of Banda Aceh, if there are elementary school (SD) students who are not from the city of Banda Aceh who wish to continue their studies to SMP / MTSN, then an al-Qur'an reading test will be carried out. So that in this problem, the researcher aims to find out the diniyah program strategies to improve students' abilities in understanding tilawatil al-Qur'an. This research uses qualitative research. The data collection techniques used were observation, interviews and documentation which were arranged in accordance with the research objectives. Based on the data collected, the researchers managed to reveal the strategy of increasing the ability of tilawatil Al-Qur'an through the diniyah program for Elementary School students (SD) Negeri 4 Banda Aceh, namely: Routine supervision, training for diniyah teachers, the school determines a learning schedule for Diniyah students, fourth and fifth grade students are required to attend the diniyah program, use audio tools to read the Koran properly and correctly, and provide motivation. Supporting factors in improving the ability of Tilawatil al-Qur'an, namely: Having full support from the Banda Aceh City Education Office, the commitment of the school principal and diniyah teachers in carrying out the diniyah program, having adequate facilities (tajwid book, library , audio, special hall and teacher), the enthusiasm of the parents, and the availability of special time to study tilawatil al-Qur'an. Keywords: Strategy, Diniyah Program, Tilawatil al-Qur'an